2017
DOI: 10.21608/ejbo.2017.777.1047
|View full text |Cite
|
Sign up to set email alerts
|

Fenugreek Seed Extract Enhanced the Growth of Vicia faba and Zea mays Seedlings

Abstract: H IGHER plants produce many phytochemical constituents that not only play a pivotal role in plants producing them, but also affect their neighboring plant communities. This study was conducted to evaluate the effect of fenugreek seed extract on the growth of faba bean (Vicia faba) and maize (Zea mays) seedlings. The allelochemical components of fenugreek seed extract were analysed and confirmed the abundance of vanillic, syringic, 4-hydroxycinnamic, sinapic, caffeic, salicylic and p-hydroxybenzoic, ferulic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…After elution with ddH 2 O, glucose, fructose, sucrose, and raffinose concentrations were measured (HPAEC-PAD) ( Vergauwen et al, 2000 ). Non-heated supernatant was used for measuring the activity of the key sugar enzymes ( Madany and Khalil, 2017 ). The activity of the invertase enzymes was measured In TAE buffer with 100 mM sucrose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After elution with ddH 2 O, glucose, fructose, sucrose, and raffinose concentrations were measured (HPAEC-PAD) ( Vergauwen et al, 2000 ). Non-heated supernatant was used for measuring the activity of the key sugar enzymes ( Madany and Khalil, 2017 ). The activity of the invertase enzymes was measured In TAE buffer with 100 mM sucrose.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction mixture containing citrate and glycogen initiated the starch synthase ( Nishi et al, 2001 ). A 0.2%v starch solution containing 0.05% of I2/KI (w/v) in 0.05% HCl was used to detect amylase activity at 620 nm ( Madany and Khalil, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…No doubt, increasing fenugreek plant density from 50 to 100% of sole cropping increased total phenols concentration in faba bean rhizosphere. It is important to mention that higher plants produce many phytochemical constituents that not only play a pivotal role in plants producing them but also affect their neighboring plant communities (Madany and Khalil, 2017). Also, they reported that the allelochemical components of fenugreek seed extract were nine phenolic compounds.…”
Section: Soil Total Phenols  Ridge Widthsmentioning
confidence: 99%
“…This biological situation will maintain leaf chlorophyll pigment from deterioration. It is known that the total leaf area of faba bean seedlings was significantly increased by increasing fenugreek extract concentration (Madany and Khalil, 2017), meanwhile, high densities of faba bean plants can cause the plants to senesce earlier (Gezahegn, 2019). Cropping Systems of Fenugreek with Faba Bean to Reduce Broomrape Infestation  The interaction between ridge widths and cropping systems Number of spikes per m 2 and their dry weight per m 2 and leaf chlorophyll b were significantly affected by the interaction between ridge widths and cropping systems in both seasons (Table 2).…”
Section:  Cropping Systemsmentioning
confidence: 99%
“…Some plant extracts or residues may inhibit germination, emergence and subsequent growth of other plants by exuding toxic substances. These substances are called allelochemicals (Madany & Khalil, 2017;Hassanein et al, 2019). When these allelochemicals are taken up by germinating seeds of the same or of other plant species, there may be some degrees of germination and emergence inhibition or growth injury (Hassanpouraghdam et al, 2010).…”
Section: Discussionmentioning
confidence: 99%